Sistem Manajemen Sanggar Seni Sarai Sarumpun Di Kota Padang - Sumiarti Darni Rahayu; Darmawati Darmawati (SENDRATASIK UNP, 2019)
This article aims to describe and explain the management system of the art workshop Sarai Sarumpun in order to manage the bun well to be able to set the schedule to appear so much in one day. This type of research is qualitative research with a descriptive method. The main instrument in this research is its own researchers and assisted with supporting instruments such as notebooks, note taking tools, video cameras, photo cameras, and tape recorders. The data types in this study are primary data and secondary data. Data collection techniques are conducted by way of library studies, observation, interviews, documentation. The steps for analyzing data are data reduction, data presentation and withdrawal of conclusions. The results showed that the management system run by the Art Gallery of Sarai Sarumpun can run well. The management system carried out by the art Snggar Sarai Sarumpun is included in the organization of the line (a form of organization where direct authority is in a vertical and fully from leadership to its subordinates). The advantage of the line organization, all decisions can be resolved directly because in a particular situation the leader becomes one of the main targets in problem solving. Disadvantages of the line organization, if there is an issue or problem can not be resolved quickly because the leader is not in place. Thus the management of the line Oganisasi to solve the problem or problems in the workshop, the head of the workshop became the first person to complete and resolve the issue.